Psychological Resilience between Existential Psychology and Islamic Sufi Thought - Melania Sarah Huwaida; Muhammad Faqih Nidzom (UIN Raden Mas Said Surakarta, 2025)
In contemporary societies marked by materialism, uncertainty, and psychological distress, the concept of psychological resilience has gained increasing scholarly attention. This study explores psychological resilience through a comparative analysis of Viktor E. Frankl’s logotherapy and Kiai Ihsan Jampes’s concept of zuhud as articulated in Sirāj al-Ṭālibīn. Employing a qualitative, library-based research design, the study analyzes primary texts: Frankl’s Man’s Search for Meaning and Kiai Ihsan Jampes’s Sirāj al-Ṭālibīn alongside relevant interdisciplinary literature. The findings reveal that although logotherapy and zuhud emerge from distinct intellectual traditions, both offer complementary frameworks for cultivating resilience. Logotherapy emphasizes the search for meaning, freedom of attitude, and responsibility in the face of suffering, while zuhud highlights detachment from excessive worldly dependence, acceptance (riḍā), and spiritual contentment. Beyond spiritual or ethical ideals, these principles function as psychological mechanisms that foster emotional regulation, inner tranquility, and adaptive coping. This study argues that integrating existential psychology with Islamic Sufi thought provides a holistic understanding of psychological resilience that bridges mental health and spiritual well-being in contemporary contexts.